2016
DOI: 10.1039/c6ob00305b
|View full text |Cite
|
Sign up to set email alerts
|

In silico screening of molecular imprinting prepolymerization systems: oseltamivir selective polymers through full-system molecular dynamics-based studies

Abstract: All-component molecular dynamics studies were used to probe a library of oseltamivir molecularly imprinted polymer prepolymerization mixtures. Polymers included one of five functional monomers (acrylamide, hydroxyethylmethacrylate, methacrylic acid, 2-(triflouromethyl)acrylic acid, 4-vinylpyridine) and one of three porogens (acetonitrile, chloroform, methanol) combined with the crosslinking agent ethylene glycol dimethacrylate and initiator 2,2'-azobis(2-methylpropionitrile). Polymers were characterized by nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…The kinetic adsorption is one of the most important factors in evaluating the adsorption efficiency. The effects of the adsorption time of the OSMIP@silica gel and NIP@silica gel for the OS solution were investigated by varying the time at a range from 10 to 300 min [ 10 , 22 ]. The kinetics adsorption curves are shown in Figure 3 a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic adsorption is one of the most important factors in evaluating the adsorption efficiency. The effects of the adsorption time of the OSMIP@silica gel and NIP@silica gel for the OS solution were investigated by varying the time at a range from 10 to 300 min [ 10 , 22 ]. The kinetics adsorption curves are shown in Figure 3 a.…”
Section: Resultsmentioning
confidence: 99%
“…Shoravi S et al also reported a preparation method of OSMIP [ 10 ]. The full-system molecular dynamics-based studies were used to screen the molecular imprinting prepolymerization systems of OSMIP.…”
Section: Introductionmentioning
confidence: 99%
“…Most MIPs are solids or soft gels, and analytical techniques to directly study the structure of individual binding sites and of individual binding events in such matrices are rare [11]. Thus, information about the binding sites is obtained using mainly indirect methods, like adsorption isotherm measurements, analysis of the pre-polymerization mixture or using computer modelling [11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The binding between the template and the monomer(s), which already exists in the pre-polymerization mixture, is expected to constitute an important part of the binding interactions with the solidified polymer. This has been one of the motivations for spectroscopic and computational studies of the pre-polymerization mixtures [22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. NMR investigation of the pre-polymerization mixture has been particularly informative concerning the stoichiometries and stabilities of pre-polymerization complexes [22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation